The Effect of Infusing Mint Leaves in First Trimester Pregnant Women on The Frequency of Nausea and Vomiting - Hasibuan, Ustifina Hasanah; Nurhayati, Nurhayati; Yunita, Sukma; Retna, Rusfita (International Journal of Nursing Information, 2023)
Common problems that often occur in first-trimester pregnant women are nausea and vomiting. Even though it is common and not detrimental to pregnant women, if it is not handled correctly, it will result in weight loss. Maintaining pregnancy is essential so that the health of the mother and future baby is maintained until the birth process. Non-pharmacological methods are the safest for dealing with this, one of which is infusing mint leaves. This study aimed to determine the effect of giving an infusion of mint leaves to pregnant women in the first trimester on reducing the frequency of nausea and vomiting. This type of research is quantitative with a pre-experimental design in one group of subjects. The number of samples was 30 pregnant women in the first trimester using purposive sampling. Research location in Pujud, Rokan Hilir, Riau, Indonesia. Statistical data analysis used the Wilcoxon test. The results of the study showed that infusing mint leaves had a significant effect on reducing the frequency of nausea and vomiting in pregnant women in the first trimester. This proves that the therapeutic benefits of mint leaves can overcome nausea and vomiting. The contribution of this research is as evidence of the benefits of infusing mint leaves and as a recommendation as an alternative therapy to reduce nausea and vomiting.